2015
DOI: 10.1007/s11430-014-4989-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of GCM cloud cover parameterizations with cloud-resolving model explicit simulations

Abstract: Three kinds of the widely-used cloudiness parameterizations are compared with data produced from the cloud-resolving model (CRM) simulations of the tropical cloud system. The investigated schemes include those based on relative humidity (RH), the semi-empirical scheme using cloud condensate as a predictor, and the statistical scheme based on probability distribution functions (PDFs). Results show that all three schemes are successful in reproducing the timing of cloud generation, except for the RH-based scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Over the past decade, CloudSat/CALIPSO have been widely used for cloud investigation and model evaluation (Luo et al, ; Yan et al, ; Yan et al, ; Yamauchi et al, ). In the cloud modeling community, a great challenge remains on how to well represent subgrid‐scale cloud condensation and fractional cloudiness (Quaas, ; Wang et al, ). Almost all climate models suffer from the poor cloudiness simulation (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, CloudSat/CALIPSO have been widely used for cloud investigation and model evaluation (Luo et al, ; Yan et al, ; Yan et al, ; Yamauchi et al, ). In the cloud modeling community, a great challenge remains on how to well represent subgrid‐scale cloud condensation and fractional cloudiness (Quaas, ; Wang et al, ). Almost all climate models suffer from the poor cloudiness simulation (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Strong dynamic cooling was observed in the upper levels along with pronounced moisture convergence in the lower levels [8]. This case has been widely used and described in previous studies [27].…”
Section: Case Introductionmentioning
confidence: 79%
“…In particular, we found that optically thick but lower‐top clouds (or thin high cirrus) significantly declined (or increased) with surface warming, especially under the unstable state. These highly biased cloud response of different cloud types from CMIP6 models implied that the cloud physics parameterization processes for corresponding low and high clouds (Wang, 2017; Wang et al., 2015) require further improvement (e.g., cumulus parameterization; Gu et al., 2020). Moreover, it remains unclear whether the reduction of optically thick but lower‐top clouds, such as cumulus congestus (one of major precipitation cloud types over TP, Liu et al., 2015), means that the precipitation over TP would decrease with surface warming.…”
Section: Discussionmentioning
confidence: 99%